Association of beta-defensin gene copy number variation with CD4 count and viral load among Malaysian ethnics hiv patients after HAART initiation - Achim, Nurfarahin Hanini (2020)
HIV is a global health concern, including in Malaysia, where more than a hundred thousand cases has been reported since 1986 until 2016. After the introduction of highly active antiretroviral therapy (HAART) regimen, HIV- related mortality and morbidity has greatly declined. Despite that, HIV clinical course were identified to be variable across population. Host genetic variation has been long recognized to have a part in influencing the susceptibility and prognosis of HIV infection. Beta-defensins gene (DEFB) encoded beta-defensins peptide, which has anti-HIV and chemoattractant properties. Interestingly, DEFB is characterized as copy number variables (CNV), a structural variation that presents in variable copy number between individuals. CNV may alter the expression of the gene and subsequently, will affect the susceptibility and progression of diseases. The CNV of DEFB has been associated with susceptibility towards a few diseases, including HIV. So far, there is still lack in information on distribution of DEFB copy number, especially among Malaysian HIV-infected patients. Moreover, the investigation on the association of DEFB CNV with CD4 count and viral load of Malaysian HIV patients are also lacking. Therefore, this study aimed to investigate the relationship of DEFB gene copy number variability with CD4 count and viral load in Malaysian HIV patients. A total of 182 HIV-infected patients and 156 controls were recruited in this study. DEFB copy number of all the participants was quantified using Triplex PRTs and validated with microsatellite analysis. DEFB copy number in HIV patients were found from 2 and 8 copies, and the modal copy number was 4. No significant difference was identified in DEFB distribution among Malay, Chinese, and Indian HIV patients. A comparison between HIV and control group found that individuals with a high copy number (> 4) are significantly higher among HIV patients as compared to controls (p = 0.039). However, no significant association was identified between DEFB copy number with the recovery of CD4 count to a normal level and viral load suppression. In conclusion, while individuals with high DEFB copy number is suggested to have higher susceptibility towards HIV, DEFB is not a significant factor in influencing the disease prognosis.